Implant setting and vestibular bone board repair - Mauricio Toro; Tomas Yoma; Alain Manuel Chaple-Gil; Eduardo Fernández Godoy (Editorial Ciencias Médicas, 2020)
Background: The occurrence of a vestibular bone lamina dehiscence of a fresh alveolus becomes a challenge for rehabilitation treatment of dental implants. Objective: To evaluate prosthetic treatment and stability of periimplant soft tissues in an alveolus with advanced oral bone resorption immediately after extraction, by using single fixed prostheses on a dental implant. Case presentation: A 29-year-old female patient, without systemic disease, completely toothed, with a thick-scalloped gingival biotype, attended the clinic and her main reason for consultation was not being aesthetically satisfied with her right upper central incisor. Radiographic examination showed advanced oral bone loss, secondary to an infection of the root of the right upper central incisor. In a first surgical phase, the right central incisor was extracted using a traumatic technique with periotomes, and a dental implant was placed. A resorbable membrane was adapted to the vestibular defect and the particulate cortical bone allograft was then compacted into the site in order to fill the space between the collagen membrane and the dental implant. A screw-retained provisional restoration was performed using the extracted natural tooth. The emergence profile was established simply by adding fluid composite resin, until the desired contours were achieved. Radiological and clinical follow-up at six months showed favorable implant evolution. No mechanical or biological complications were observed during this observation period. The oral gingival margin was in a correct position. Conclusion: This technique allowed predictable aesthetic-functional outcomes and soft tissue stability in a thick-scalloped gingival biotype with a single fixed prosthesis.